Fixation and Release of Intact E4 Tetrahedra (E=P, As)1. Issue 14 (10th February 2015) - Spitzer, Fabian; Sierka, Marek; Latronico, Mario; Mastrorilli, Piero; Virovets, Alexander V.; Scheer, Manfred
Abstract: By the reaction of [NacnacCuCH3 CN] with white phosphorus (P4 ) and yellow arsenic (As4 ), the stabilization and enclosure of the intact E4 tetrahedra are realized and the disubstituted complexes [(NacnacCu)2 (μ, η 2:2 ‐E4 )] (1 a : E=P, 1 b : E=As) are formed. The mono‐substituted complex [NacnacCu(η 2 ‐P4 )] (2 ), was detected by the exchange reaction of1 a with P4 and was only isolated using low‐temperature work‐up. All products were comprehensively spectroscopically and crystallographically characterized. The bonding situation in the products as intact E4 units (E=P, As) was confirmed by theory and was experimentally proven by the pyridine promoted release of the bridging E4 tetrahedra in1 . Abstract : Too fragile? Just wrap it! Sensitive P4 and As4 can be stabilized in [(NacnacCu)2 (μ, η 2:2 ‐E4 )] (E=P, As), which serves as storage material. The E4 tetrahedra are intact, which was confirmed by calculations and experimentally by liberation with a Lewis base (LB). [NacnacCu(η 2 ‐P4 )] was also isolated, which contains an intact, side‐on coordinated P4 entity. Its dynamic behavior was examined by different NMR techniques.